A21 RANDOMIZED PROSPECTIVE STUDY: IMPACT OF THE PATIENT EDUCATION WEBSITE ON THE QUALITY OF OUTPATIENT BOWEL PREPARATION FOR COLONOSCOPY:. (1st March 2018) - Suzuki, M M; Bardi, M; Takach, O; Galorport, C; Yonge, J; Harris, N; Lam, E; Telford, J J; Rosenfeld, G; Ko, H; Enns, R A
Abstract: Background: Low level bowel cleanliness that occurs in 25% of patients, hinders polyp detection and limits colonoscopy effectiveness. Those with inadequate preparation have incomplete examinations, fewer polyps detected, more repeat colonoscopies and higher resource utilization. Aside from pharmacological and timing of purgative factors to optimize bowel preparation, non-pharmacological factors that influence patient compliance (i.e. patient education) in the preparation phase can significantly improve bowel preparation quality. Aims: To assess if interactive, individualized web based instruction leads to improved colonoscopy preparation through enhanced patient compliance, satisfaction and tolerability of preparation. Methods: A randomized, prospective, single blinded trial initiated at St. Paul's hospital in Vancouver, B.C. Inclusion criteria: age >19, planned outpatient colonoscopy, and willingness/ability to participate by reading the online English material supplied by sending the subject a specific domain (which contains the educational information for their colonoscopy). Exclusion criteria: None. Consecutive patients enrolled into the study (target of 450 participants). Data Collected: demographics, cancellations, bowel preparation cleanliness scores as per Boston bowel preparation score (BBPS) and Ottawa bowel preparation score. Primary end points: percentage of patients that achieve an excellent BBPS following web-based instructions vs paper instructions. Assessment of patient satisfaction, preparation tolerability and patient activation score through post colonoscopy follow-up surveys. Results: 450 patients have been recruited and analyzed. 197 are male; mean age 55 years (range 20–81). 223 were assigned to Group A (paper based) and 227 to Group B (web based). A Fisher's exact test showed a significant difference in the proportion of subjects achieving an excellent BBPS score ≥8 (Group A = 37% (82/223), Group B = 47% (106/227) p=0.0357) and a significant decrease in the number of subjects with inadequate preps BBPS≤3 (Group A = 8.9% (20/223), Group B = 3.5% (8/227) p=0.0191). There was no significant difference in patient satisfaction (p=0.8415), helpfulness (p=0.9847) or clarity of instructions (p=0.8936). Conclusions: Analysis showed a significant difference in patients achieving both excellent and inadequate bowel preparation scores between interactive individualized web based instructions vs written instructions. Due this study our office has transitioned to using the web platform as standard of care. We are currently running an open label study to continue monitoring the outcomes of patient using the web platform. Funding Agencies: None